UPAYA PREVENTIF DENGAN ERGONOMI PARTISIPATORI MENINGKATKAN PEMAHAMAN DAN PERILAKU MASYARAKAT TERHADAP RABIES DI DESA CEPAKA KEDIRI TABANAN - Ni Ketut Dewi Irwanti; Ni Luh Putu Agustini Karta; Made Christin Dwitrayani (Synergy and Society Service, 2023)
In 2022 rabies cases in Bali will experience a sharp increase, this condition shows that the government program has not been successful in achieving zero rabies. Therefore, a socialization and education program in community service was carried out by Triatma Mulya University in Cepaka Village, Tabanan, Bali as a form of Higher Education's concern for the environment. Preventive efforts are carried out using a participatory ergonomics approach involving all stakeholders from the government, academics, experts, community leaders, animal lovers groups and the community. The success of the community service program can be seen from the enthusiasm of the residents to take part in the activity. There were 56 residents who took part in the activity with 94 animals that were vaccinated, sterilized or castrated and from the pretest and posttest questionnaires conducted, it was obtained an increase in people's understanding and behavior towards rabies. The average increase in people's understanding of rabies is 7.47. Whereas in the behavior variable towards rabies, there is an average increase of 4.57.